Identifikasi Porotic Hyperostosis dan Cibra Orvitalia pada Temuan Rangka (Studi Kasus Review) - pribadi, anjar; Sauma, Anis Khoirun; Amin, Muhammad Taufiq (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 14 No 2 (2024): Indonesian Journal of Legal and Forensic SciencesDO - 10.24843/IJLFS.2024.v14.i02.p04, 2025)
Forensic anthropology is a specialized field within anthropology that aims to identify individuals based on available evidence, such as determining characteristics like race, gender, approximate age, height, body shape, unique features, health status, time and cause of death, as well as reconstructing facial features. Individualized data, including patterns of diseases, can offer insights into the individual's life. Common conditions like pathological porotic hyperostosis and cibra orvitalia often leave lesions on the skull and eye sockets, yet no such lesions were found on the skeletal remains in the suitcase.